Assessment of body fat percentage and its associated factors among hospitalized elderly - Zainol, Anis Syakirah; Omar, Noraida; Mohamad Shafie, Shazli Ilyani; Norhi’sham, Siti Hazimah (UPM Press, 2022)
Introduction: Elevated body fat percentage among elderly has resulted in a significant number of morbidity and mortality. Thus, this study aimed to determine the body fat percentage and its associated factors among hospitalized elderly in Klang Valley hospitals. Methods: A total of 57 subjects aged ≥ 60 years were recruited from the geriatric wards of three Klang Valley hospitals (Hospital Sungai Buloh, Hospital Tengku Ampuan Rahimah and Hospital Kuala Lumpur) using purposive and convenience sampling. A face-to-face interview and physical examination were conducted to obtain the data on socio-demographic characteristics, medical background, anthropometric measurements, total cholesterol levels, hand-grip strength, perception towards oral health, dietary assessment and malnutrition risk. The body fat percentage was assessed using a handheld bio-electrical impedance OMRON HBF-302 and compared with Gallagher’s classification of body fat percentage. A simple descriptive statistic and correlation analysis were used to analyze the body fat percentage and its associated factors. Results: Majority of hospitalized elderly (49%) had elevated body fat percentages. Weight (p≤0.0005), BMI (p≤0.0005), and malnutrition risk (p≤0.0005) were significantly associated with the body fat percentage. Meanwhile, other variables were not significantly associated with body fat percentage in hospitalized elderly. Conclusion: Weight, BMI, and malnutrition risk were found to be significantly associated with the body fat percentage. Other variables were not significantly associated. Thus, a better understanding of factors associated with body fat percentage is necessary in managing elevated body fat percentage to reduce the risk of morbidity and mortality among hospitalized elderly.